Factores que influyen en el rendimiento académico de residentes de Obstetricia y Ginecología de una universidad en Bogotá, Colombia (2019)
Postgraduate training in medicine, known as Residence, is a period of high demand for the medical practitioner. The academic performance of this professional can be affected by some socioeconomic, psycho-affective and other factors that depend on the characteristic of the postgraduate program. To evaluate the influence of these factors on residents of Obstetrics and Gynecology of an university, a cross-sectional descriptive study was performed. The factors with the greatest influence on academic performance were those of having a constant motivation and have their own and family economic stability. In the evaluation of psycho-affective factors, the factors with the highest positive responses were the consideration that the primary function as a resident is to learn, the perception that exams do not really assess what they have learned and the fact of facing emotional problems in the hospital with calm. All residents said they have never been victims of constant intimidation, harassment, offenses or attacks by any of their partners. In conclusion, several factors have a very important influence on the academic performance of this group of residents, mainly their own economic stability and of the other family members, constant motivation, being in a learning function, calmly handling emotional problems and the appreciation that exams do not really assess what they have learned. These factors must be taken into account, because in addition to affecting the resident’s training they can also interfere with patient care and identifying them can promote wellness programs for these professionals.